Toxicological Profiling and ADME In Silico Characterization of Volatile Organic Compounds in Traditional Rice Beer and Starter Cultures - Bharadwaj, Bhriganka; Das, Shourish; Bhowal, Arnab; Bora, Payel; Boro, Sangita; Sarmah, Rajeev (International Journal of Aquatic Research and Environmental Studies, 2026)
Traditional ethnic fermented beverages and their starter cultures contain a complex matrix of volatile organic compounds (VOCs) that dictate both flavor profiles and potential xenobiotic risks. This study presents a comprehensive toxicological screening, target prediction, and in silico ADME (Absorption, Distribution, Metabolism, and Excretion) profiling of eight volatile compounds identified in traditional rice beer and starter cakes. Evaluation via AMES mutagenicity tests, hepatotoxicity modeling, and human Maximum Tolerated Dose (MTD) parameters revealed a complex risk hierarchy where analytical abundance does not linearly correlate with biological danger. Pharmacokinetic modeling identified a distinct metabolic baseline: compounds exhibiting high baseline toxicity but characterized by high excretion rates (70%-85%) and low 24-hour tissue retention (15% 22.5%), such as nitro-tert-butyl-acetate, pose severe acute exposure challenges but clear rapidly. Crucially, the data demonstrate that the absolute physiological hazard is governed by the intersection of high structural toxicity and low clearance dynamics. Compounds with low excretion rates (55%) and high 24-hour retention profiles (45%), most notably the blood-brain barrier (BBB) permeant (phenylmethyl)-hydrazine, pose the most significant long-term systemic threats due to prolonged tissue persistence and irreversible monoamine oxidase (MAO) inhibition. Conversely, high-risk compounds with low intestinal absorption thresholds and high excretion rates fail to achieve the systemic bioaccumulation required to inflict extensive cellular or organ-level damage. Consequently, safety intervention strategies should move beyond baseline quantitative reductions. Targeted processing interventions, such as specialized downstream filtration or temperature-regulated volatilization steps, must be developed to selectively isolate and filter out high-retention, brain-permeant mutagens from the finished beverage, thereby preserving traditional fermentation heritages while mitigating chronic public health risks.